PENAHANAN ANAK YANG BERKONFLIK DENGAN HUKUM DALAM PERSPEKTIF HAK ASASI MANUSIA - Yudistira, Rizal; Suhartono, Slamet; Herlin Setyorini, Erny (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
â€Article 4 of the Child Protection Act that every child has the right to live, grow and participate properly and participate in accordance with human dignity and dignity, and get protection from violence and discrimination . The problem in this study is how the characteristics of children in conflict with the law can be detained. The research method used is normative legal research.